ROUTINE ENDOSCOPY BEFORE BARIATRIC SURGERY; NECESSITY OR OVERKILL (Journal of Medical & Health Sciences Review, 2025)
Background: We aim to determine the frequency of patients with abnormal preoperative esophagogastroduodenoscopy (EGD) and factors associated with it in patients undergoing bariatric surgery to assess their impact on surgical planning. Methods: A cross-sectional study was conducted at the Department of Surgery at a tertiary care hospital from October 2024 to March 2025. Patients planned for bariatric surgery with age between 16 and 70 years, BMI ≥ 27.5 kg/m² and ASA I-III who consented for preoperative EGD were included. EGD was performed by consultant gastroenterologists for abnormal EGD findings and data was collected by a surgical resident.Results: A total of 159 patients were included in the study, with a preponderance of females 92 (57.9%). The mean age was 39.7 years, and the median BMI was 44.5 kg/m² (IQR 37.90 - 53.60). OSA (50.9%) and hypertension (49.1%) were the most common comorbidities. Abnormal EGD findings were reported in 21/159 (13.2%) patients. Gastritis was the most common finding in 14/159 (8.8%) patients, followed by ulcers in 9/159 (5.7%) patients. Among the 21 patients with abnormal findings, five (23.8%) patients required a change in their planned surgical procedure. Stratified analysis showed that GERD and NSAID use were significantly associated with abnormal EGD findings.Conclusion: Our study suggests that routine EGD is not necessary for all bariatric surgery patients due to the low prevalence of abnormal findings. EGD should be selectively performed in patients with a history of GERD and NSAID use to guide surgical decisions and improve postoperative care.